Corn Husk Lamp Box / Nurfatin Hanafi...[et.al] - Hanafi, Nurfatin; Elias, Noor Emyra; Harun, Nurul Fatihah; Mohd Sobri, Nurul Masniza (Faculty of Plantation and Agrotechnology, 2016)
Technology today has made a much more direct impact to the end user especially in daily life, without technology our life like in the darkness. Therefore, d.Light Enterprise appeared as a technology and innovation concept of company that produce decoration lamp. Our business is a partnership form of business consisting of five partners which are also act as partners .